A game for the ages: Understanding and overcoming the relative age effect in Australian football. Issue 2 (April 2023) - Barake, Adrian J; Mitchell, Heather; Stavros, Constantino; Stewart, Mark F
The Relative Age Effect (RAE) in sport refers to the over-representation of those born earlier in a defined age group. This discriminatory effect leads to market inefficiencies and can have profound impacts upon career pathways, dropout rates and the quality of sport. This research examines how this effect influences the recruitment and performance of a cohort of Australian footballers as they progress from junior competitions to the professional level. While the RAE results from bias influencing the selection process of junior pathways, we demonstrate that those who survive to the final stages of selection and were born later in their age groups actually emerge with an advantage (rather than the expected disadvantage). The selection of these younger players results from recruiters explicitly taking account of the RAE. When the performance of these advantaged players is assessed at the professional level, they perform relatively well, suggesting that the recruiters are expertly considering the consequences of the RAE; although their task would be considerably easier if they were not dealing with a legion of young footballers whose characteristics had already been heavily shaped by the RAE. We consider a range of implications of this effect and suggest policy measures to address it.